MATERIKLER HÁM OKEANLAR TÁBIYIY GEOGRAFIYASÍ KURSÍN OQÍTÍWDA INTERAKTIV METODLARDAN PAYDALANÍW - Tolepov, E.T.; Gaypova, R.T. (SCIENCE and SOCIETY, 2022)
This article, the main attention will be paid to improving the methods of formation of knowledge, skills and abilities of students in school geography lessons using interactive methods, as well as improving the level of thinking and the effectiveness of the lesson.